TANDA TANGAN ELEKTRONIK DALAM PELAKSANAAN TUGAS POKOK DAN FUNGSI LEMBAGA PERADILAN - Sudarsono; Abdul Halim (Jurnal Hukum Peratun, 2019)
One of the important elements in the Electronic Court System (e-Court) is the electronic signature as regulated in article 26 of the Supreme Court Regulation No. 1 of 2019. In addition to the electronic litigation system, electronic signatures will also be very useful in the implementation of basic tasks of the judiciary, both in trial administration and general administration of the court. This research will discuss electronic signature in court administration as the main topic and will be elaborated with several related topics which include the task of the judicial institution, the electronic signature in the judicial system, person in charge of electronic signature in court administration, and the validity of documents with an electronic signature. The result of the research shows that electronic signature is crucial on implementation of court functions which are judicial function, regulatory function, and executive function performed by the court. Electronic signature creates the process of the case, trial, and general administration in court become more effective, efficient, and eco-friendly, and it also will increase public trust and security of the electronic transaction. Judicial documents that are electronically signed by authorized officials have legal force and legal consequences that can be used for legal remedies, evidence, and so on. For these reasons, it is necessary for the Supreme Court issuing the regulation on the implementation of electronic signatures in judicial institutions in performing their main tasks and functions.